Isolation and Characterization of Two Bacteriophages and Their Preventive Effects against Pathogenic Vibrio coralliilyticus Causing Mortality of Pacific Oyster (Crassostrea gigas) Larvae - Hyoun Joong Kim; Sib Sankar Giri; Sang Guen Kim; Sang Wha Kim; Jun Kwon; Sung Bin Lee; Se Chang Park (Microorganisms, 2020)
Vibrio coralliilyticus is one of the major pathogens causing mass mortality in marine bivalve larvae aquaculture. To prevent and control Vibrio spp. infections in marine bivalve hatcheries, various antibiotics are overused, resulting in environmental pollution and the creation of multi-drug-resistant strains. Therefore, research on the development of antibiotic substitutes is required. In this study, we isolated two bacteriophages (phages) that specifically infected pathogenic V. coralliilyticus from an oyster hatchery and designated them as pVco-5 and pVco-7. Both phages were classified as Podoviridae and were stable over a wide range of temperatures (4–37 °C) and at pH 7.0–9.0. Thus, both phages were suitable for application under the environmental conditions of an oyster hatchery. The two phages showed confirmed significant bactericidal efficacy against pathogenic V. coralliilyticus in an in vitro test. In the in vivo experiment, the phage pre-treated groups of Pacific oyster larvae showed significantly lower mortality against V. coralliilyticus infection than untreated control larvae. The results of the present study suggest that both phages could be used in the artificial marine bivalve seedling industry; not only to prevent pathogenic V. coralliilyticus infection, but also to reduce antibiotic overuse.